Suffering For Science : Reason and Sacrifice in Modern America - Herzig, Rebecca M., 1971- (Book collections on Project MUSE., 2005)
From gruesome self-experimentation to exhausting theoretical calculations, stories abound of scientists willfully surrendering health, well-being, and personal interests for the sake of their work. What accounts for the prevalence of this coupling of knowledge and pain-and for the peculiar assumption that science requires such suffering? In this lucid and absorbing history, Rebecca M. Herzig explores the rise of an ethic of "self-sacrifice" in American science. Delving into some of the more bewildering practices of the Gilded Age and the Progressive Era, she describes when an.